DYSTOCIA DUE TO SCHISTOSOMA REFLEXUS IN A NON DESCRIPTIVE DOE - KUMARI, G .ARUNA; KUMARI, ROOH UL AMIN; KUMARI, ROOH UL AMIN; TEJA, A; RAO , K SADASIVA (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to Schistosoma reflexus of the kid in a goat and its successful per vaginal delivery is described in this report.